Względy estetyczne przy wyborze imion = Aesthetic considerations when selecting names - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the considerations in this article are the aesthetic considerations accompanying the choice of names. This motivation plays an important role today. However, it is not easy to define what aesthetic considerations are. The author decided to take a closer look at them. The research, including the speeches of language researchers and parents` reflections, reflected in online commentary and forum posts, covered several areas: graphic, phonetic, word-formation and semantic.
Keywords: antroponimia; motywacje wyboru imion; względy estetyczne; forma graficzna; brzmienie imion; tworzenie zdrobnień; asocjacje; anthroponomastics; motives for choosing names; aesthetic reasons; graphic form; sound of names; formation of diminutives; associations